2019
DOI: 10.1002/ana.25475
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation: Connectivity profile for bradykinesia alleviation

Abstract: Objective: Subthalamic deep brain stimulation may alleviate bradykinesia in Parkinson patients. Research suggests that this stimulation effect may be mediated by brain networks like the corticocerebellar loop. This study investigated the connectivity between stimulation sites and cortical and subcortical structures to identify connections for effective stimulation. Methods: We retrospectively investigated 21 patients with Parkinson disease with bilateral subthalamic deep brain stimulation. Stimulation effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…The clinical effects of DBS, such as improvement in parkinsonism and SID, may ultimately reflect the sum of the effects through different mechanisms. Connectivity profiles associated with postoperative motor improvement in PD patients have been reported, 13,16,31,32 and those associated with stimulation‐induced adverse effects (ie, SID, dysarthria, and psychiatric manifestations) may also be essential for achieving better overall clinical outcomes. Connectivity studies may clarify the mechanism of action of DBS.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical effects of DBS, such as improvement in parkinsonism and SID, may ultimately reflect the sum of the effects through different mechanisms. Connectivity profiles associated with postoperative motor improvement in PD patients have been reported, 13,16,31,32 and those associated with stimulation‐induced adverse effects (ie, SID, dysarthria, and psychiatric manifestations) may also be essential for achieving better overall clinical outcomes. Connectivity studies may clarify the mechanism of action of DBS.…”
Section: Discussionmentioning
confidence: 99%
“…DT can define specific axonal trajectories as the basis of pathwayactivation models to provide better anatomical/electrical volume conductor estimations to evaluate the strength and coverage of electric field covering DBS targets (Gunalan et al, 2018). As such, DT helped strategize the best direct or indirect DBS target by delineating and segmenting STN-cortical (Chen et al, 2018;Gunalan et al, 2018), pallido-cortical (Middlebrooks et al, 2018), pedunculopontine (Raghu et al, 2021), and cortico-cerebellar pathways (Strotzer et al, 2019;Coenen et al, 2020) to mitigate PD-related motor symptoms and minimize unwanted side effects, such as depression and impaired cognition (Combs et al, 2015;Irmen et al, 2020).…”
Section: Deep Brain Stimulation Therapy For Parkinson's Diseasementioning
confidence: 99%
“…Specifically, the authors showed that the postoperative outcome of STN-DBS is strongly associated with active stimulation of contacts connected to the primary cortex and supplementary motor area and that can be individually defined. In addition, both DTI profile and network-based connectivity have served as a preoperative predictor for postoperative outcome (Koirala et al, 2018;Gonzalez-Escamilla et al, 2022) or a targeted indicator to trace the therapeutic effect (Strotzer et al, 2019;Huang et al, 2022).…”
Section: Deep Brain Stimulation Therapy For Parkinson's Diseasementioning
confidence: 99%
“…stimulation spread to corticobulbar fibers, 15,17 or both, involvement of the pyramidal tract and cerebello-thalamic fibers. 16,35 The involvement of these two All rights reserved. No reuse allowed without permission.…”
Section: Structural Network Associated With Sidmentioning
confidence: 99%